Retrograde Flexible Ureteroscopic Approach for Pyelocaliceal Calculi - Geavlete, Petrisor; Seyed Aghamiri, Seyed Abdulah; Multescu, Razvan (Urology Journal, 2009)
Introduction: Our goal was to investigate the efficacy of flexible ureteroscopy (FU) in the treatment of pyelocaliceal calculi. Materials and Methods: Between September 2002 and December 2004, a total of 41 patients with multiple (23 cases), pelvic (7 cases), and inferior caliceal (11 cases) SWL-resistant calculi underwent FU. We used a 7.5-F flexible ureteroscope with pressure irrigation and electro-hydraulic lithotripsy. The fragments were retrieved with triradiate graspers or tipless baskets. Results: A double J stent had been previously placed in 34% of the patients. Dilation of the ureteral orifice was necessary in 9.8%. The location of the calculi was renal pelvis, inferior calyx, and pelvis and calyxes in 7, 11, and 23 patients, respectively. The median operative time was 64 minutes for pyelocaliceal, 46 minutes for pelvic, and 39 minutes for inferior caliceal calculi. Complete stone clearance or good fragmentation (fragments less than 3 mm) was obtained in 71% of patients (57% for pyelocaliceal, 87% for pelvic, and 71% for inferior caliceal calculi). A successful outcome was achieved in 78%, 72%, and 49% for calculi sized 10 mm or smaller, 11 mm to 20 mm, and greater than 20 mm, respectively. Two or more procedures were required in 11 patients (27%). The complication rate was 7.3% (hematuria, persistent renal colic, and hyperthermia). Conclusion: Our experience shows that FU can be an effective approach in selected patients, especially those with kidney calculi that are resistant to SWL. However, percutaneous approach is a better alternative for calculi greater than 20 mm.